2016
DOI: 10.1016/j.pedn.2016.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' Beliefs Regarding Pain in Critically Ill Children: A Mixed-Methods Study

Abstract: Purpose The purpose of this study was to provide a current and comprehensive evaluation of nurses’ beliefs regarding pain in critically ill children. Design and Methods A convergent parallel mixed-methods design was used. Nurse beliefs were captured via questionnaire and interview and then compared. Results Forty nurses participated. Most beliefs reported via questionnaire were consistent with effective pain management practices. Common inaccurate beliefs included the need to verify pain reports with physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 25 publications
2
5
0
2
Order By: Relevance
“…Similar opinion was presented by nurses surveyed by Dongara et al. () and LaFond, Van Hulle Vincent, Oosterhouse, and Wilkie (). However, such assumption is erroneous taking into account the results published by Donovan, Dillon, and McGuire (); according to these authors, sleeping problems were reported mostly by patients with a mild subjective pain, whereas those with a severe subjective pain claimed that they slept normally.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Similar opinion was presented by nurses surveyed by Dongara et al. () and LaFond, Van Hulle Vincent, Oosterhouse, and Wilkie (). However, such assumption is erroneous taking into account the results published by Donovan, Dillon, and McGuire (); according to these authors, sleeping problems were reported mostly by patients with a mild subjective pain, whereas those with a severe subjective pain claimed that they slept normally.…”
Section: Discussionsupporting
confidence: 78%
“…Unfortunately, administration of opioid therapy in children is still consider less safe than in adults, probably due to an erroneous assumption that it may often result in respiratory depression. This myth is another barrier to effective pain control (LaFond et al., ) since having a choice between lower and higher dose of an opioid agent, most nurses will likely choose the lower one. Opioid treatment of pain is generally safe (Tomaszek et al., ) with 0.5% or less episodes of respiratory depression (Dahan et al., ; Walker, ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, LaFond et al. 's () study suggested 42.5% of nurses ( n = 40) believed that children did not reliably report pain. Vincent et al.…”
Section: Resultsmentioning
confidence: 99%
“…A dor é um fenômeno subjetivo que sofre influências de variáveis fisiológicas e psicológicas, sendo uma experiência única para cada indivíduo 6 . A intensidade dos estímulos dolorosos pode sofrer interferências de aspectos culturais, bem como da percepção do observador, sendo importante estar atento às crenças e valores individuais e familiares durante a avaliação da dor 7 .…”
Section: Referencial Teóricounclassified
“…Para se identificar corretamente a dor na criança deve-se levar em consideração o nível cognitivo, bem como a condição clínica da mesma 9 . Devido ao seu caráter subjetivo, fica a critério da enfermeira considerar a genuinidade da queixa álgica, fator esse que interfere no cuidado prestado frente a essa queixa, pois é diretamente proporcional ao conhecimento, as atitudes e as crenças das profissionais, atuando como uma bússola 18 . Contudo, ao avaliar a dor na criança, a profissional deve atentar para as crenças errôneas, internalizando a ideia de que a intensidade da dor é menor do que em um adulto, ou que não se lembrarão da experiência de dor 2 .…”
Section: (E2)unclassified